A role for TSPO in mitochondrial Ca(2+) homeostasis and redox stress signaling - Gatliff, Jemma (Cell Death Dis, 2017)
The 18 kDa translocator protein TSPO localizes on the outer mitochondrial membrane (OMM). Systematically overexpressed at sites of neuroinflammation it is adopted as a biomarker of brain conditions. TSPO inhibits the autophagic removal of mitochondria by limiting PARK2-mediated mitochondrial ubiquitination via a peri-organelle accumulation of reactive oxygen species (ROS). Here we describe that TSPO deregulates mitochondrial Ca(2+) signaling leading to a parallel increase in the cytosolic Ca(2+) pools that activate the Ca(2+)-dependent NADPH oxidase (NOX) thereby increasing ROS. The inhibition of mitochondrial Ca(2+) uptake by TSPO is a consequence of the phosphorylation of the voltage-dependent anion channel (VDAC1) by the protein kinase A (PKA), which is recruited to the mitochondria, in complex with the Acyl-CoA binding domain containing 3 (ACBD3). Notably, the neurotransmitter glutamate, which contributes neuronal toxicity in age-dependent conditions, triggers this TSPO-dependent mechanism of cell signaling leading to cellular demise. TSPO is therefore proposed as a novel OMM-based pathway to control intracellular Ca(2+) dynamics and redox transients in neuronal cytotoxicity.